Problematika Anak Tunarungu dalam Pembelajaran PAI di SLB Negeri 1 Kulon Progo - Sari, Dwi Nur Indah; Khoirunnisa, Jany Fitria; Hafidhdin, Aswin Nurjanah Muhammad; Mahmuda, Ibnu; Husna, Difa’ul (MASALIQ, 2023)
Learning is a process of interaction between educators and students in a learning environment to achieve educational goals. The purpose of Islamic religious education is for students to understand and practice Islamic teachings in accordance with the Al-Qur'an and sunnah, and to maximize their role as servants and caliphs of Allah. In achieving the goal of Islamic religious education is certainly not easy especially when teaching deaf children. Where the deaf child has a hearing loss so it is difficult to receive information. In this article, the authors conducted research at SLB Negeri 1 Kulon Progo using a qualitative descriptive approach, with the case study method and data collection techniques through interviews with PAI teachers and observation in deaf groups of 20 children. The purpose of this study is to find out the problems for deaf children in learning Islamic religious education at SLB Negeri 1 Kulon Progo. The results of this study are true that there are problems in learning Islamic religious education for deaf children. Among them are many Islamic religious education subject matter that are abstract in nature so that it is difficult to explain visually, difficult conditioning, limitations in reading, and remembering the material.